Pengaruh Komitmen Organisasional dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Bali Funtastic di Ubud, Gianyar - Puguh Wahyudi, Dewa Gede; Surya Diputra, Gde Indra (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Employee performance is strongly supported by human resources or employees who work, the higher the employee's commitment to continue working well, it is able to improve the company's work results, besides that satisfied employees will be happy to work and affect their performance. The purpose of this study is to determine the effect partial and simultaneous effect of organizational commitment and job satisfaction on employee performance. The location of this study was conducted at Bali Funtastic, with a total sample of 32 employees using the saturated sampling method. The data collection method uses observation, interviews, literature studies, and questionnaires. Analytical technique by conducting instrument tests followed by classical assumption tests, coefficients of determination, f-test, and t-test. The results of this study where organizational commitment has a positive and significant effect on employee performance. Job satisfaction has a positive and significant impact on employee performance. Simultaneously, organizational commitment and job satisfaction positively and significantly affect employee performance. Advice for subsequent researchers to improve employee performance by fostering organizational commitment and increasing job satisfaction of all employees.